Pengaruh Aturan Etika Dan Independensi Terhadap Kepuasan Kerja Internal Auditor (Studi pada Auditor Pemerintah di BPKP PerwakilanProvinsi Lampung) - Linda (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2018)
BPKP representative of Lampung province is one of the working units of the financial and development supervisory board a non-departemental government institution domiciled under and directly responsible to the president. What is needed from internal auditor is a broad view and an understanding of the managerial and human related processes, which underlie the internal function of auditors. The accountant profession is inseparable from business ethics whose activities need understanding and application of professional ethics of an accountant as well as business ethics. Ethical rule is a collection of principles or moral values that become a handle for a person or a group in regulating its behavior. In addition, the auditor shall be independent of any obligation or independent of the ownership of interst in the audited company. The purpose of this research is to know how the influence of ethics rule and independency to internal work satisfaction of auditor at BPKP representative of Lampung province, this research use primary data, that is data obtained directly from original source with questionnaire. The method used is nonprobability sampling. The result of hypothesis testing states that the rule of ethics partially does not affect the job satisfaction with value -0.227<1.674 and independence have an effect on job satisfaction with value 4.851>1.674. Simultaneously the rules of ethics and independence have an effect on the internal work satisfaction of auditor with value 57.890>value 2.78. Then the contribution of independent variabel (X) to dependent (Y) is its influence 69.4% while the rest 30.6% job satisfaction influenced by other variable outside regression model in this research. This shows that ethich and independent rules are very important to be applied in order to improve the auditor’s ability in carrying out the main task and function as a public accountant.